2008
DOI: 10.2460/ajvr.69.12.1580
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a dimethyl sulfoxide–stabilized frozen canine platelet concentrate

Abstract: Results of this in vitro study indicated that there was a decrease in platelet quantity and function as well as an increase in platelet activation during the freeze-and-thaw process in DMSO-stabilized canine frozen PC. In vivo effects on PC remain to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…48 This study identified decreases in platelet number and function as a result of the freeze-and-thaw process. 48 This study identified decreases in platelet number and function as a result of the freeze-and-thaw process.…”
Section: Cryopreserved Canine Platelet Concentratementioning
confidence: 84%
“…48 This study identified decreases in platelet number and function as a result of the freeze-and-thaw process. 48 This study identified decreases in platelet number and function as a result of the freeze-and-thaw process.…”
Section: Cryopreserved Canine Platelet Concentratementioning
confidence: 84%
“…The presence of the platelets in the samples likely increased clot strength through their physical integration into the forming clot and by providing additional phosphatidylserine expressing surfaces for the assembly of coagulation factor complexes thereby accelerating clot formation . It is likely that few of the platelets survived the freeze/thaw process despite the presence of the dimethyl sulfoxide . At the time of collection, our PRP samples contained a high number of platelets in an attempt to account for the anticipated loss due to the freeze/thaw process.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their ease of use in clinical settings and apparent efficacy in this case series, the authors consider cryo‐PRP an appropriate option for managing CSS. After freeze‐thaw, canine cryo‐preserved platelets externalize PS . It is possible that these platelets provide an advantage to fresh platelets in promoting thrombin generation in CSS patients.…”
Section: Discussionmentioning
confidence: 99%
“…After freeze-thaw, canine cryo-preserved platelets externalize PS. 17 It is possible that these platelets provide an advantage to fresh platelets in promoting thrombin generation in CSS patients. However, the shorter half-life of cryopreserved platelets may necessitate higher doses or repeated transfusion versus fresh PRP.…”
Section: Discussionmentioning
confidence: 99%